Prevention of Miscarriage of Justice in the Implementation of Judges’ Tasks - Tetania Retno Gumilang; Victoria Tabita Majesty Lamada (Jurnal Hukum Prasada, 2020)
Work by relying on conscience, to decide whether someone is guilty or not. The judge profession is one of the noble professions. The judge determines a person's actions. Judges are called noble, clearly addressing this profession has a higher degree. In convicting a criminal, besides at least two valid evidence, a judge's conviction is needed. The judge is called the representative of God on earth. However, judges are still ordinary people who are not free from mistakes. Miscarriage of justice happens a lot in the decisions they make. This study examines the prevention of miscarriage of justice in the implementation of judges’ tasks. This research is designed by using normative-juridical method, which is an approach that uses a positivist-juridical conception, namely that law is identical with written norms created by the authorities, so far the law is made as a normative system that is autonomous closed and independent of people's lives. The results show that Justice is something aspired by the people of Indonesia. Judges are the most important element in realizing justice that is highly aspired. Judges as representatives of God who hold to the "For the sake of justice based on the Almighty God" develop a difficult task. Many miscarriage of justice occurs in the community. Judges as a profession that has a higher degree must hold on to professional ethics to avoid miscarriage of justice.